Peripheral Neuropathy and HIV Infection - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The prevalence and patterns of peripheral neuropathy in 50 children with HIV infection were analyzed retrospectively in the EMG Section, National Institutes of Health, Bethesda, MD.